Cretaceous-Paleogene rifting on the NW margin of the Australian continent, SE Banda Arc region - Charlton, Timothy (Ikatan Ahli Geologi Indonesia, 2023)
The Banda Terrane successions of Timor Island and correlative units in Sumba are widely considered allochthonous with respect to the Australian continental margin successions that form the main part of the Banda arc-continent collision complex. A new interpretation is proposed for the Banda Terrane, which suggests that these units originated on the outermost (northern) edge of the Australian continent. Volcanic successions in the Banda Terrane, which date to the Cretaceous and Paleogene (Aptian/Albian to Eocene), are interpreted as originating in a backarc/marginal basin setting behind a northward-facing arc that rifted away from the NW margin of Australia through this period. The Banda terrane successions are interpreted as representing the southern, continent-attached portion of the marginal basin, and occupied a position on the distal edge of Australia up to the onset of Banda arc-continent collision in the Miocene.Supporting evidence for an Australian margin origin of the Banda Terrane includes very similar age ranges for zircons dated to the Cretaceous in Sumba and Timor (Banda Terrane) and in sandstones of the Ungar Formation in Tanimbar, the latter forming an element of the Australian margin succession. In Timor there is also previously reported evidence for continental margin rifting during the Late Cretaceous, while contemporaneous Late Cretaceous-Paleogene volcanism is also recognised in the Bird’s Head-Misool region of eastern Indonesia, which forms part of the Australian continental margin. In addition, a number of stratigraphic links between the Banda Terrane and the Australian continental margin successions in Timor are summarised in this study.The effects of the Cretaceous-Paleogene rifting event are also apparent in subsidence curves derived from petroleum exploration wells drilled on the northern ‘passive’ continental margin of Australia from SW of Timor to the Bird’s Head-Misool region of eastern Indonesia. Inferred rift-related subsidence commenced in the Aptian-Albian on the Australian palaeo-margin immediately east of Timor and developed sporadically but in regionally consistent groupings throughout the Late Cretaceous and Paleogene.